276 Relationship Between Water Use Efficiency and Feedlot Steer Performance and Health. (8th October 2021) - Bruno, Kelsey; Ahlberg-Smith, Cashley; McPhillips, Levi J; Meador, Heather; Taylor, Alex; Calvo-Lorenzo, Michelle S; Desilva, Udaya; Krehbiel, Clint; Mateesku, Raluca; Place, Sara; Rolf, Megan M; VanOverbeke, Deb; et al.
Abstract: As climate change progresses, it is expected that water availability for livestock production will be challenged due to competition from human population growth and use by other agricultural sectors. The objective of this study was to evaluate differences in animal performance and health between feedlot steers with differing water use efficiencies. Four groups of steers from numerous sources (n = 469) were randomly allocated to 2 body weight (BW) blocks. Individual feed and water intake (WI) were measured daily using an Insentec RIC feeding system. Steers had ad libitum access to feed and water for 70 d (BAS). After a 28 d step-down period, steers were maintained at 50% of ad libitum water consumption for 42 d (RST) while feed continued to be offered ad libitum. Based on average daily water intake during BAS, steers were sorted into low, medium, or high-water use efficiency (LWE, MWE, or HWE) using k-means clustering. Every 14 d BW was collected in addition to blood samples for complete blood counts. Body weight was used to evaluate ADG and G:F. Data were analyzed using the GLIMMIX procedure of SAS with the model statement including effects of water use efficiency, day, and the interaction. Body weights were greater in HWE than MWE and LWE at the end of BAS and RST (P < 0.01). Steer ADG and G:F were greater in HWE compared to MWE and LWE (P < 0.01)during BAS, but not different during RST (P > 0.54). Hematocrit and red blood cell counts initially increased during water restriction step down, and then returned to normal levels (P < 0.01); these values were also greater in HWE compared to MWE and LWE (P < 0.01). All steers adapted to limited water access similarly and the degree of health differences had little clinical significance.